Prosecution under articles 2 and 3 of the Corruption Law and Supreme Court Regulation No. 1/2020 - Faisal, Emir; Yuliati, Yuliati; Madjid, Abdul (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the urgency of amending Supreme Court Regulation No. 1 of 2020 concerning Guidelines for the Imposition of Penalties under Articles 2 and 3 of the Corruption Criminal Law (Perma 1/2020). This study uses a normative legal research method with a legislative approach, a case approach, and a comparative law approach. Perma 1/2020 is a responsive measure to address the issue of unwarranted disparity in corruption criminal case rulings. However, to date, the application of Perma 1/2020 has not been consistently applied by judges in adjudicating corruption offenders, particularly those involved in Articles 2 and 3 of the Corruption Criminal Law. Therefore, stronger legal reinforcement is needed to ensure that Perma 1/2020 can be consistently implemented in every criminal corruption case decision.